Identification of Introgressed Alleles Conferring High Fiber Quality Derived From Gossypium barbadense L. in Secondary Mapping Populations of G. hirsutum L. - Chen, Yu; Liu, Guodong; Ma, Hehuan; Song, Zhangqiang; Zhang, Chuanyun; Zhang, Jingxia; Zhang, Junhao; Wang, Furong; Zhang, Jun (Frontiers in Plant Science, 2018)
The improvement of fibre quality is an essential goal in cotton breeding. In our previous studies, several quantitative trait loci (QTLs) contributing to improved fibre quality were identified in different introgressed chromosomal regions from Sea Island cotton (Gossypium barbadense L.) in a primary introgression population (Pop. A) of upland cotton (G. hirsutum L.). In the present study, to finely map introgressed major QTLs and accurately dissect the genetic contribution of the target introgressed chromosomal segments, we backcrossed two selected recombinant inbred lines (RILs) that presented desirable high fibre quality with their high lint-yielding recurrent parent to ultimately develop two secondary mapping populations (Pop. B and Pop. C). Totals of 20 and 27 QTLs for fibre quality were detected in Pop. B and Pop. C, respectively, including four and five for fibre length, four and eight for fibre micronaire, two and four for fibre uniformity, five and four for fibre elongation, and six and four for fibre strength, respectively. Two QTLs for lint percentage were detected only in Pop. C. In addition, seven stable QTLs were identified, including two for both fibre length and fibre strength and three for fibre elongation. Five QTL clusters for fibre quality were identified in the introgressed chromosomal regions, and negative effects of these chromosomal regions on lint percentage (a major lint yield parameter) were not observed. Candidate genes with a QTL-cluster associated with fibre strength and fibre length in the introgressed region of Chr.7 were further identified. The results may be helpful for revealing the genetic basis of superior fibre quality contributed by introgressed alleles from G. barbadense. Possible strategies involving marker-assisted selection (MAS) for simultaneously improving upland cotton fibre quality and lint yield in breeding programmes was also discussed.